2019
DOI: 10.1080/02656736.2019.1640899
|View full text |Cite
|
Sign up to set email alerts
|

Intraprocedural contrast-enhanced ultrasound-CT/MR fusion imaging assessment in HCC thermal ablation to reduce local tumor progression: compared with routine contrast-enhanced ultrasound

Abstract: Purpose: To evaluate whether local tumor progression (LTP) would be further reduced when contrastenhanced ultrasound (CEUS)-CT/MR fusion imaging was used as intraprocedural assessment method in hepatocellular carcinoma (HCC) thermal ablation compared with routine CEUS. Materials and methods: This prospective non-randomized study was conducted from December 2010 to July 2012. CEUS-CT/MR fusion imaging and routine CEUS were used for treatment response assessment in the ablation procedure of 146 HCCs and 122 HCCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 43 publications
0
28
1
Order By: Relevance
“…Expanding or overlapping ablation was performed to ensure that all the tumors were ablated at least 0.5 cm beyond the tumor margin when possible [25,26]. Artificial ascites were created before RFA which acted as an insulation layer between the tumor(s) and the adjacent vital structures such as gallbladder, diaphragm, pericardium, liver capsule and gastrointestinal tract [24,27,28]. After the lesions were ablated, the ablation path was cauterized to avoid tumor seeding and hemorrhage.…”
Section: Rfa Proceduresmentioning
confidence: 99%
“…Expanding or overlapping ablation was performed to ensure that all the tumors were ablated at least 0.5 cm beyond the tumor margin when possible [25,26]. Artificial ascites were created before RFA which acted as an insulation layer between the tumor(s) and the adjacent vital structures such as gallbladder, diaphragm, pericardium, liver capsule and gastrointestinal tract [24,27,28]. After the lesions were ablated, the ablation path was cauterized to avoid tumor seeding and hemorrhage.…”
Section: Rfa Proceduresmentioning
confidence: 99%
“…Consequently, some assisted methods were adopted to achieve complete ablation (21,22). In recent years, many studies have confirmed that the ablation margin is closely related to local recurrence (23,24). Thus, evaluation of the ablation margin becomes more and more important in the clinical treatment of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of liver cancer is associated with hepatitis B and c virus infection, aflatoxin, drinking water pollution, alcohol, liver cirrhosis, sex hormones, nitrosamines and trace elements (24)(25)(26). However, the pathogenesis and treatment of liver cancer is still unclear (27,28). Therefore, it is of great significance to study the regulatory mechanism of liver cancer tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%